COVID-19 pandemic and mortality in nursing homes across USA and Europe up to October 2021 - Aalto, Ulla L; Pitkälä, Kaisu H; Andersen-Ranberg, Karen; Bonin-Guillaume, Sylvie; Cruz-Jentoft, Alfonso Jose; Eriksdotter, Maria; Gordon, Adam L; Gosch, Markus; Holmerova, Iva; Kautiainen, Hannu; Kivipelto, Miia; Macijauskiene, Jurate; et al. (European geriatric medicine, 2022)
PURPOSE: We compared the prevalence of COVID-19 and related mortality in nursing homes (NHs) in 14 countries until October 2021. We explored the relationship between COVID-19 mortality in NHs with the average size of NHs and with the COVID-19 deaths at a population level. METHODS: The total number of COVID-19 cases and COVID-19-related deaths in all NHs as well as the total number of NHs and NH beds were provided by representatives of 14 countries. The population level respective figures in each country were provided up to October 2021. RESULTS: There was a wide variation in prevalence of COVID-19 cases and deaths between countries. We observed a significant correlation between COVID-19 deaths in NHs and that of the total population and between the mean size of NHs and COVID-19 deaths. CONCLUSION: Side-by-side comparisons between countries allow international sharing of good practice to better enable future pandemic preparedness.
Keywords: COVID-19; Pandemics; Humans; lidé; Nursing home; pečovatelské domovy; Evropa; Europe; pandemie; SARS-CoV-2; Mortality; Nursing Homes